Effects of interactive metronome and golf swing mechanics training on technique and motor timing in professional and amateur golfers - Kim, J. H.; Ridgel, A. L. (International Journal of Sports Science & Coaching, 2019)
Accurate motor timing is required to produce well-coordinated movements during the golf swing. We developed the Interactive Metronome protocol, which included golf swing mechanics to improve motor timing. Thirty golfers were recruited into a category based on their experience: (a) professionals who qualified to play in the Professional golf tournament (n = 10) and (b) amateurs who played in the college golf tournament (n = 20). The amateur group was then randomized into either an intervention or control group. The intervention groups completed 12 sessions of Interactive Metronome with golf swing mechanics. During Interactive Metronome with golf swing mechanics training, golf swing mechanics were practiced with both audio and visual timing cues. The control group completed golf swing training only. Motor timing and golf mechanics were measured before and after the training. There was a significant time by group interaction (p = 0.048) in the coordination of the upper limbs where the professional and amateur groups showed a significant improvement compared with the control (p = 0.048). There was a main effect of time and a significant improvement in overall motor timing (p < 0.001), hand and feet (p < 0.01) timing, and balance (p = 0.003) from pre to post test. Club speed (p = 0.008), club path variability (p = 0.009), and smash factor (p < 0.001) showed a main effect of group where the professional golfers showed greater smash factor and club speed and less variability than the amateur golfers. These findings suggest that Interactive Metronome with golf swing mechanics can improve coordination in limbs and golf swing mechanics.